Flood Risk Pattern Recognition Analysis in Klang River Basin - Nor Ain Kandari, Puteri; Shakir Mohd Saudi, Ahmad; Jyh Chyang, Pang; Khairul Amri Kamarudin, Mohd; Hafiz Md Saad, Muhammad; Azid, Azman; Surayya Mohd Saudi, Nur; Mahmud, Muaz (International Journal of Engineering and Technology, 2018)
This study was implemented to identify the specific factors that lead to major contribution of floods in Klang River Basin. A thirty-year (1987-2017) database obtained from Department of Irrigation and Drainage (DID), the selected data was analyzed by using integrated Chemometric techniques. The finding from Correlation Analysis revealed strong correlation between stream flow and water level is more than 0.5 (= 0.799). The finding from Principal Component Analysis proved that the selected parameters were significant with the result of R2 > 0.7was applied as a main tool for further analysis. Based on the result, it revealed that stream flow and water level were the most significant hydrological factor that influenced flood risk pattern in Klang River basin. Based on the result from Statistical Process control (SPC), the finding showed that the Upper Control Limit (UCL) for water level was 30.290m. The plotted data which is more than 30.290 m can cause flood to occur in Klang River Basin. Thus, it is very important to continuously monitor and maintain the mitigation measure of flood in the study area to avoid flood to occur. This study also helps to provide visualization of flood pattern and show the optimal rates for the maximum limit for flood control in Klang River Basin.Â Â